2018
DOI: 10.1002/marc.201800250
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Induced Cationic Polymerization of Epoxides by Using Multiwalled Carbon Nanotubes

Abstract: The visible light induced cationic polymerization of epoxides can be achieved by means of multiwalled carbon nanotubes (MWCNTs), which act as visible light photoinitiators via a radical-induced cationic photopolymerization process. When MWCNTs are irradiated with longer wavelengths (above 400 nm), they generate carbon radicals, by means of hydrogen abstraction from the epoxy monomer; these radicals are oxidized in the presence of iodonium salt to a carbocation that is sufficiently reactive to start the cationi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…In order to match with the wavelength requirements for certain practical applications, the sensitivity range of onium salts was extended to higher wavelengths by using free radical photoinitiators, charge transfer complexes, and singlet and triplet photosensitizers . It was also shown that nanoparticles and highly conjugated molecules can also sensitize cationic polymerization by photoinduced electron transfer reactions. Among all these strategies, so‐called free radical promoted cationic polymerization outlined in Scheme is most widely used methodology as many free radical photointiators acting at broad wavelength range are readily available.…”
Section: Methodsmentioning
confidence: 99%
“…In order to match with the wavelength requirements for certain practical applications, the sensitivity range of onium salts was extended to higher wavelengths by using free radical photoinitiators, charge transfer complexes, and singlet and triplet photosensitizers . It was also shown that nanoparticles and highly conjugated molecules can also sensitize cationic polymerization by photoinduced electron transfer reactions. Among all these strategies, so‐called free radical promoted cationic polymerization outlined in Scheme is most widely used methodology as many free radical photointiators acting at broad wavelength range are readily available.…”
Section: Methodsmentioning
confidence: 99%
“…In their studies, Sangermano et al [ 87 ] demonstrated the effect of multi walled carbon nanotubes (MWCNT) as free radical generator induced by visible light for the cationic polymerization of bis-cycloaliphatic epoxy using diaryliodonium salt. The mechanism involves a cationic polymerization of epoxides through visible light generated electrons and holes from MWCNTs ( Figure 3 A), followed by electron transfer reactions with the iodonium salt ( Figure 3 B) [ 87 ].…”
Section: Onium Salt Photoinitiators For Different Epoxy Monomersmentioning
confidence: 99%
“…Fors [33,34], Nicewicz [35], and Boydston [36] et al found that pyrylium salts can drive the polymerization of vinyl ethers, 4-methoxystyrene, and norbornenes, through cationic pathways or ring-opening metathesis mechanisms. Yagci et al [37,38,39,40,41,42,43,44] developed visible light-cationic and radical polymerizations using various non-metallic materials. Even so, the very limited category and quantity of organic photocatalysts have motivated researchers to exploit new organic catalysts.…”
Section: Introductionmentioning
confidence: 99%